Severe haemolysis associated with hepatitis A and normal glucose-6-phosphate dehydrogenase status. Issue 7 (July 1990) - Lyons, D J; Gilvarry, J M; Fielding, J F
Abstract : We report massive acute haemolysis associated with hepatitis A in a 36 year old Irish woman. Although mild anaemia is not uncommon during viral hepatitis, haemolysis of the severity observed in this patient has previously been reported only in patients with glucose-6-phosphate dehydrogenase deficiency.